The Europa world year book. - Europa Publications Limited (London Europa Publications, 1989)
Annual
Issued in two volumes.
Title varies: 1958-1988 Europa yearbook.
Keywords: International agencies -- Periodicals; Economic history -- 1945- -- Periodicals; Organizations -- Periodicals; World politics -- 1989- -- Periodicals